2013
DOI: 10.4172/2329-8863.1000103
|View full text |Cite
|
Sign up to set email alerts
|

Phenolic Compounds from Diluted Acid Hydrolysates of Olive Stones: Effect of Overliming

Abstract: Annually, important quantities of olive residue are produced and may be the source of ecological damages. Like agricultural residues, which are abundant, renewable, low cost raw materials, olive stones are mainly subjected to biotechnological or chemical modifications in order to be transformed into valuable products (biofuels, biofertilizers, animal feed and chemical feed-stock). In aim to valorize olive stones, we are trying to identify the presence of different phenolic compounds in their dilute-acid hydrol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 29 publications
1
0
0
Order By: Relevance
“…The HPLC-DAD analysis of prehydrolyzates showed the presence of antioxidant compounds such as protocatechuic acid, vanillin, vanillic acid, homovanillic acid and 3,4dimethoxybenzoic acid (Fig. 6), which is in agreement with reports by Andary et al (2013). Rubio-Senent et al (2013) have demonstrated that fractions rich in some of these compounds have a high antiradical capacity comparable to α-tocopherol or reducing power values higher than Trolox.…”
Section: Antioxidant Capacitysupporting
confidence: 90%
“…The HPLC-DAD analysis of prehydrolyzates showed the presence of antioxidant compounds such as protocatechuic acid, vanillin, vanillic acid, homovanillic acid and 3,4dimethoxybenzoic acid (Fig. 6), which is in agreement with reports by Andary et al (2013). Rubio-Senent et al (2013) have demonstrated that fractions rich in some of these compounds have a high antiradical capacity comparable to α-tocopherol or reducing power values higher than Trolox.…”
Section: Antioxidant Capacitysupporting
confidence: 90%